Melatonin Target Proteins: Too Many or Not Enough? - Liu, Lei; Labani, Nedjma; Cecon, Erika; Jockers, Ralf (Frontiers in Endocrinology, 2019)
The neurohormone N-acetyl-5-methoxytryptamine, better known as melatonin, is a tryptophan derivative with a wide range of biological effects that is present in many organisms. These effects are believed to rely either on the chemical properties of melatonin itself as scavenger of free radicals or on the binding of melatonin to protein targets. More than 15 proteins, including receptors (MT1, MT2, Mel1c, CAND2, ROR, VDR), enzymes (QR2, MMP-9, pepsin, PP2A, PR-10 proteins), pores (mtPTP), transporters (PEPT1/2, Glut1), and other proteins (HBS, CaM, tubulin, calreticuline), have been suggested to interact with melatonin at sub-nanomolar to millimolar melatonin concentrations. In this review we assemble for the first time the available information on proposed melatonin targets and discuss them in a comprehensive manner to evaluate the robustness of these findings in terms of methodology, physiological relevance, and independent replication.